2016
DOI: 10.1111/1744-7917.12306
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time cell analysis and heat shock protein gene expression in the TcA Tribolium castaneum cell line in response to environmental stress conditions

Abstract: The rust red flour beetle, Tribolium castaneum (Herbst, 1797) (Coleoptera: Tenebrionidae), is a pest of stored grain and one of the most studied insect model species. Some of the previous studies involved heat response studies in terms of survival and heat shock protein expression, which are regulated to protect other proteins against environmental stress conditions. In the present study, we characterize the impedance profile with the xCELLigence Real-Time Cell Analyzer and study the effect of increased temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(109 reference statements)
0
5
0
1
Order By: Relevance
“…This is in agreement with recent findings. When the cells were is exposed to 40°C heat shock for 1 h, although Tchsp18.3 , Tchsp68a and Tchsp83 were significantly up‐regulated as a similar expression pattern, Tchsp18.3 seems to be the most affected (Garcia‐Reina et al ., ). This phenomenon could also be found when beetles were under mild heat shock; Tchsp18.3 was up‐regulated higher than Tchsp68 (Altincicek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is in agreement with recent findings. When the cells were is exposed to 40°C heat shock for 1 h, although Tchsp18.3 , Tchsp68a and Tchsp83 were significantly up‐regulated as a similar expression pattern, Tchsp18.3 seems to be the most affected (Garcia‐Reina et al ., ). This phenomenon could also be found when beetles were under mild heat shock; Tchsp18.3 was up‐regulated higher than Tchsp68 (Altincicek et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Quantitative real‐time polymerase chain reaction (real‐time qPCR) analysis of transcriptional levels of this species‐specific shsp were up‐regulated when the beetles were in response to septic wounding, heat shock and UV‐A exposure, suggested that it was involved in immunity and stress responses (Altincicek et al ., ; Sang et al ., ). Additionally, when cell line BCIRL‐TcA‐CLG1 of T. castaneum was treated with heat shock, increased salinity, acidic pH and UV‐A light, hsp18.3 ( hsp27 ) seems to be the most affected by 40°C and UV light other than hsp68a and hsp83 (Garcia‐Reina et al ., ). Hsp18 .3 seems to be an important one in terms of cell growth and viability of T. castaneum , but there are no studies carried out with its systematic functions in T. castaneum , and whether it has a functional differentiation is still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…In the corn stalk borer Sesamia nonagrioides , the transcription level of Hsp83 was rapidly up‐regulated by 40°C heat stress, in which 15 to 30 min induced a 15‐fold up‐regulation (Gkouvitsas et al ., ). Also, in Tribolium castaneum cell growth and viability, 1 h of 40 °C exposure up‐regulated expression of Hsp83 (García‐Reina et al ., ). In P. melete , results indicate that Hsp90 reached almost maximum expression levels within 30 min of heat shock.…”
Section: Discussionmentioning
confidence: 97%
“…Insect species, as ectotherms, are susceptible to various environmental stresses such as extreme temperatures, oxidation, heavy metal exposure and other abiotic factors. As molecular chaperones, HSPs play important roles in helping organisms cope with various ambient stresses (Arya et al, 2007;Garcia-Reina et al, 2017;Lu et al, 2017;Tian et al, 2018). A total of 25 HSPs have been identified from the C. lividipennis genome, including three HSP90, eight HSP70, six HSP60 and eight sHSP genes.…”
Section: Heat Shock Protein Genesmentioning
confidence: 99%